2011
DOI: 10.1109/tvlsi.2010.2041377
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Comparison in the Energy-Delay-Area Domain of Nanometer CMOS Flip-Flops: Part II—Results and Figures of Merit

Abstract: In Part II of this paper, a comparison of the most representative flip-flop (FF) classes and topologies in a 65-nm CMOS technology is carried out. The comparison, which is performed on the energy-delay-area domain, exploits the strategies and methodologies for FFs analysis and design reported in Part I. In particular, the analysis accounts for the impact of leakage and layout parasitics on the optimization of the circuits. The tradeoffs between leakage, area, clock load, delay, and other interesting properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…Post-layout simulations showed that the kit's estimates for small designs are often conservative and that compact circuits often perform slightly faster in post-layout simulations than in schematic simulations with the automatic parasitic network estimation turned on. The simulation test bench that is used in this comparison is very similar to the ones used in [5], [13], [14]. The Q output of a simulated flip-flop is connected to a load of four symmetric inverters with their n-type transistors sized at minimum recommended width.…”
Section: Previous Work Existing Methodsmentioning
confidence: 99%
“…Post-layout simulations showed that the kit's estimates for small designs are often conservative and that compact circuits often perform slightly faster in post-layout simulations than in schematic simulations with the automatic parasitic network estimation turned on. The simulation test bench that is used in this comparison is very similar to the ones used in [5], [13], [14]. The Q output of a simulated flip-flop is connected to a load of four symmetric inverters with their n-type transistors sized at minimum recommended width.…”
Section: Previous Work Existing Methodsmentioning
confidence: 99%
“…The charge keeper circuit for the internal node can be saved due to the addition of pull-up pMOS transistor. With the circuit simplicity, this approach also keep down the load capacitance of node X [14], [15].…”
Section: Addition Of Pull-up Pmos Transistor -mentioning
confidence: 99%
“…Accordingly, Clock-gated FFs are unsuitable for nanometer technologies. Among [3] DET FFs, the DET-TGLM represents the most energy-efficient solution in the deep low-energy region, together with TGFF. It is the DET counterpart of TGFF and they show similar performances since the greater layout complexity of DET-TGLM is compensated by the energy reduction due to the DET property.…”
Section: Related Workmentioning
confidence: 99%
“…It has longer data to Q delay compared to CDFF. Since three stacked transistor is used it faces worst case delay [3]. To overcome this delay a pull down circuitry is used but the disadvantage is that extra layout area and power consumption.…”
Section: Existing Designsmentioning
confidence: 99%
See 1 more Smart Citation